MENTAL WORKLOAD OF AIR TRAFFIC CONTROL (ATC) PERSONNEL AT ADISUTJIPTO INTERNATIONAL AIRPORT - Seftiyana, Via Choirul (Institut Teknologi Dirgantara Adisutjipto, 2021)
Air traffic controllers are under excessive stress because of their job. This has been linked to aspects of ATC work such as high job demands, time or responsibility pressure, or inadequate equipment. Types of work that require more vigilance, such as air traffic controllers at airports, are closely related to mental jobs that require high concentration. Because there is a negative impact on a company if it gives mental workload too high or too low for its employees, it is necessary to measure it to find out the right mental workload for its employees. This study aims to calculate the mental workload felt by ATC personnel in the APP unit. Measurement of mental workload in this study using the NASA-TLX (National Aeronautics and Space Administration Task Load Index). This method measures 6 (six) dimensions of workload size, namely Mental Demand, Physical Demand, Temporal Demand, Performance, Effort and Frustation Level